Role of Service Quality on Deciding Customer Satisfaction: A factor in Health Care Services: Exploring the Impact of Service Quality on Customer Satisfaction in Healthcare (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Some people are of opinion that customer satisfaction leads to recognition of service quality, whereas there are others who think that service quality leads to customer satisfaction. Additionally, the connection between customer satisfaction and service quality and their interrelation in purchasing behaviour is greatly unexplored. Service quality is a key factor for customer satisfaction, which is the basis for true loyalty. Thus, the purpose of this is to look at the role of service quality on deciding customer satisfaction when it comes to health care services.